Influence of Corporate Attributes on Magnitude of Disclosure by Private Commercial Banks in Bangladesh - Rahman, Md Tahidur; Uddin, Mohammad Main (Journal of Business and Technology (Dhaka), 2017)
The study reports the results of an empirical investigation of the magnitude of disclosure by listed Private Commercial Banks (PCBs) in Bangladesh and the attributes influencing it. For the purpose of the study, samples were taken following the purposive sampling approach covering about 21 percent of the population. A researcher developed unweighted disclosure checklist containing 247 information items divided into ten groups, were utilized. Applying the Dichotomous scoring procedure, the study found an average disclosure of 75.76 percent with a constant growth during the study period. Significant differences were found while comparing the disclosure level among the years and among the sample banks under study. Out of the eight variables, the regression model used in the study found Log total assets, Return on Equity (ROE), and EPS as three influential contributors to disclosure; while other five variables were found to have insignificant influence on disclosure of PCBs in Bangladesh. Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 111-118